Comparación entre el inicio de vasopresores de forma temprana vs convencional en la mortalidad del paciente séptico con hipotensión en el servicio de emergencia del Hospital Víctor Lazarte Echegaray en el año 2020 - Brito Martinez, Henry José (2020)
The purpose of this research is to compare the mortality of septic patients with hypotension in whom vasopressor infusion is administered early versus those in whom it is administered after fluid correction, in which it will be determined whether there is a reduction in blood pressure. mortality after titration of these. The values of mean arterial pressure, serum lactate, mental status and urinary flow will be monitored, in order to then follow up the patient and thus compare mortality at 24 hours and at 28 days after hospital admission in both study groups.